107 Email alerts allow more rapid assessment by palliative care service and decrease length of hospital stay for those discharged home. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Curtis, Hannah; Smith, Rob; England, Ruth
Abstract : Background: The Hospital Palliative Care Team (HPCT) at Royal Derby Hospital identified a number of circumstances where previously known patients were readmitted, but not promptly re-referred, to HPCT. The average length of time between admission to hospital and referral to HPCT was 8 days. We believed earlier HPCT intervention might reduce length of stay. Methods: Through our electronic hospital database we attach an e-alert to a patient's clinical details which generates an email on each re-admission. HPCT apply e-alerts to the records of patients who have stated they would not want further hospital admissions or to those complex patients for whom we feel early involvement in future would be advantageous. We check the e-alert inbox daily and respond by telephoning the ward to ascertain whether HPCT input is required. Results: We report on data collected over 30 months relating to 627 unique patients with e-alerts. 213 patients had unplanned re-admissions to hospital. A total of 294 emails were received, on average 2.25 emails per week – which did not present an excessive new workload. HPCT response time to an e-alert averaged 0.6 days. For those patients whose preference was to be discharged, the use of an e-alert was associated with a reduced time in hospital of 7 days. When the patient died in hospital, the average length of stay was 15 days. Conclusion: Admit alerts allow HPCT to make a more prompt assessment of patients previously known to the service. For patients who go on to be discharged home, this is associated with a decreased length of hospital stay. We suggest this may improve patient experience.